Digitalization of Victim and Damage Data Collection Due to Flash Floods in Alukuta Village as a Basis for Data-Based Disaster Mitigation - Akmal Izwar; Nuraida Nuraida; Reza Fahmi; Muliani Muliani; Irwansyah Irwansyah (ABDISAINS, 2026)
Flash floods that occurred in Alukuta Village, Bireuen Regency, caused significant social and economic impacts on the affected community, including human impacts and material damage. One of the main challenges in post-disaster conditions is the lack of accurate and well-classified data, which often leads to inappropriate aid distribution, particularly for vulnerable groups such as infants, toddlers, pregnant women, breastfeeding mothers, and the elderly. This community service activity aimed to collect data on victims and damage caused by flash floods using an information system–based approach to support targeted aid distribution and disaster mitigation at the village level. The methods used included primary data collection through questionnaires, interviews, and direct field observations. The collected data were analyzed descriptively and presented through an information system and infographics. The results showed that there were 285 displaced persons from 77 households, with a high proportion of vulnerable groups, as well as damage to houses, village infrastructure, and community livelihoods. The information system–based data collection facilitated better understanding of actual field conditions by volunteers and donors, enabling more appropriate aid distribution. This activity is expected to serve as a model for post-disaster data collection to support data-driven disaster mitigation at the village level. Keywords: flash flood, disaster data collection, information system, vulnerable groups, disaster mitigation